Comparing feeling of competence regarding humanistic caring in Belgian nurses and nursing students: A comparative cross‐sectional study conducted in a French Belgian teaching hospital. Issue 1 (2nd September 2020) - Lecocq, Dan; Delmas, Philippe; Antonini, Matteo; Lefebvre, Hélène; Laloux, Martine; Beghuin, Amélie; Van Cutsem, Chantal; Bustillo, Aurélia; Pirson, Magali
Abstract: Aim: The aim of the study was to describe and compare feeling of competence regarding humanistic caring in Registered Nurses (RN) and nursing students (NS). Design: A quantitative comparative cross‐sectional research design was used. Methods: A convenience sample of 196 RN and 47 NS in a teaching hospital in Belgium completed a self‐administered questionnaire composed of a sociodemographic survey and the Caring Nurse‐Patient Interactions Scale (CNPI‐23) developed by Cossette et al. Results: The four dimensions of the CNPI‐23 were compared using the Skillings–Mack test. Both groups scored higher on "humanistic" and "comforting" than on "clinical" and "relational" care and both scored lowest on this last dimension. Linear regressions showed that none of the variables had a statistically significant influence on the CNPI‐23 scores, except for NS "state of health, " which influenced their feeling of competence regarding "relational care."